Role Playing Strategies to Foster Empathy and Mutual Respect Among Elementary School Students - Juny Mona Morlina; Ahmad Ta'rifin (FITK UIN Walisongo Semarang, 2026)
This study aims to determine the improvement of the character of mutual respect among fifth-grade students after the implementation of the role-playing strategy in each learning cycle. The study used a Classroom Action Research (CAR) approach implemented in several cycles. Research data were collected through tests in each cycle, observations, questionnaires, and document analysis. Data analysis techniques were carried out descriptively qualitatively and quantitatively to observe the development of students' character at each stage of the action. The results showed that the initial condition of the character of mutual respect among students was still relatively low. In the pre-cycle stage, most students had not shown optimal attitudes of empathy, cooperation, and respect for peers due to learning that was still conventional and minimal social interaction. The implementation of the role-playing strategy in cycle I began to show positive changes through increased student participation in groups, courage to express opinions, and a more active learning atmosphere, although the results were not evenly distributed. In cycle II, the improvement in the character of mutual respect occurred significantly after the role-playing scenario was made more structured and closer to real situations. The percentage of students with character categories reached 79%, marked by increased attitudes of empathy, cooperation, and respect for friends' opinions. Retention data one month after learning showed that 89% of students maintained mutual respect behavior in their daily lives. These findings demonstrate that role-playing strategies are effective in shaping students' social character in a significant, sustainable way, and based on real-life social experiences. This research contributes to the strengthening of the use of role-playing strategies as a character-based learning innovation that can foster active learning while simultaneously instilling social values ​​sustainably in elementary school students. Keywords: role-playing, mutual respect, elementary school students